Generalizing the Real Interval Arithmetic - CALLEJAS-BEDREGAL, R.; BEDREGAL, B.R.C.; SANTIAGO, R.H.N. (Trends in Computational and Applied Mathematics, 2002)
In this work we propose a generalized real interval arithmetic. Since the real interval arithmetic is constructed from the real arithmetic, it is reasonable to extend it to intervals on any domain which has some algebraic structure, such as field, ring or group structure. This extension is based on the local equality theory of Santiago [11, 12] and on an interval constructor which mappes bistrongly consistently complete dcpos into bifinitely consistently complete dcpos.